Acute exercise is not cardioprotective and may induce apoptotic signalling in heart surgery: a randomized controlled trial. (13th February 2018) - Smenes, Benedikte T; Bækkerud, Fredrik H; Slagsvold, Katrine H; Hassel, Erlend; Wohlwend, Martin; Pinho, Maria; Høydal, Morten; Wisløff, Ulrik; Rognmo, Øivind; Wahba, Alexander
Abstract: OBJECTIVES: During open-heart surgery, the myocardium experiences ischaemia–reperfusion injury. A single bout of moderate, 30-min exercise induces preconditioning and protects the heart from ischaemia–reperfusion injury in rats, but this has never been investigated in humans. We aimed to investigate whether 1 bout of moderate exercise 24 h prior to surgery protects against mitochondrial and cardiac damage. METHODS: Patients scheduled for elective coronary artery bypass were eligible for this pilot study. Twenty were included and randomized to the treadmill exercise group (the EX group, n = 10) 24 h preoperatively or to standard presurgical procedures (control n = 10). Right atrial (RA) and left ventricular (LV) biopsies were collected immediately before and as long as possible after aortic cross-clamping to assess the primary outcome of mitochondrial respiration by respirometry, in addition to reactive oxygen species production by fluorometry and apoptotic transcripts. Cardiac troponin T and creatine kinase myocardial brain were measured in plasma at arrival, before surgery and 6 and 24 h postoperatively. RESULTS: Mitochondrial respiration was lower in the EX group after surgery in the LV (Complex I −22%, P < 0.05 and maximal −23%, P < 0.05) and the right atrium (Complex I −25%, P < 0.05). Transcript level of the apoptosis-related marker caspase 3 was increased 1.5-fold in the LV prior to surgery in the EX group when compared with the control group, P < 0.05. Cardiac troponin T was 45% higher in the EX group than in the control group 6 h postoperatively ( P = 0.03), although not significant when corrected for aortic cross-clamping time. CONCLUSIONS: Results indicate that exercise did not precondition the heart against surgery-related damage. Exercise may render the myocardium and mitochondria more vulnerable to perioperative damage. Clinical trials registration number: NCT00218985 (https://clinicaltrials.gov/ct2/show/NCT00218985 )